STRATEGI PEMASARAN ONLINE JASAPINDAH.ID BERBASIS INTEGRATED MARKETING COMMUNICATION (IMC) - Maharani Ayuning Tyas; Amanah Rakhim Syahida (Jurnal Ilmu Komunikasi Balayudha, 2022)
This study uses mediamorphosis theory and marketing communication to explain how Jasapindah.id's marketing communication strategy is in marketing through online media. This research method is descriptive qualitative with triangulation data collection which includes interviews, observations and literature. This study uses three sources, namely Supervisor, Business and Development Manager, and digital marketing staff of Jasagerak.id as key informants to obtain primary data. After the primary data is found, then it is analyzed using the elements of Integrated Marketing Communication (IMC).The results of this study indicate that Jasapindah.id is active in implementing marketing communication strategies through online media. The marketing strategy using the Integrated Marketing Communication (IMC) strategy is carried out as a step in business development. This is a strategy to increase the number of website visitors and build brand awareness as an effort to increase turnover from Jasapindah.id.